Propagation of surface cracks on beam blank in the mould during continuous casting. (21st October 2019) - Yang, Gaiyan; Zhu, Liguang; Chen, Wei; Yu, Xingwang; Guo, Gaoxiang
ABSTRACT: We focus on crack propagation to investigate surface cracks in the mould during continuous casting, based on the crack initiation mechanism proposed in previous studies. The temperature and stress data of a solidified shell were extracted, and an extended finite element model based on the continuous damage theory of elastic–plastic materials was developed to simulate surface crack propagation. The results showed that, in the cracked area, stress concentration occurred at the crack tip, and the element split open and the crack propagated when the maximum principal stress in the stress concentration area reached the critical value. Prefabricated cracks in the fillet and web mainly developed into longitudinal cracks in the mould. The theoretical mechanism of this study was found to be the same as the crack propagation mechanism observed during the actual production of beam blanks. Thus, this study reveals the theoretical principle of crack initiation and propagation and can provide theoretical guidance for controlling surface cracks during beam blank continuous casting.